Academic success of type i and type ii alcoholics children - Akbaş, Seher; Tütüncü, Emel; Tamar, Müge; Coşkunol, Hakan; Kesikçi, Hande (Journal of Dependence, 2003)
Objective: In this study, alterations in the children’s academical success according to parents alcoholism type was investigated by using Cloninger’s alcoholizm typology.Method: Sociodemographic Data Form I, SCID I, Michigan alcoholizm Screening Test (MAST) were applied to fathers who were free from alcohol at least for one month and had completed detoxification treatment in the Alcohol and Drug Addiction Departmen of the Ege University Medical Faculty. According to data and Cloninger’s alcoholism typology, types of alcoholic fathers were determined in Alcohol and Drug Department. Psychiatric interview was made with children who were between 8-12 years old of these alcoholics parents by using DSM IV diagnostic criteria. Sociodemographic Data Form II was aplied to children, Children Depression Inventory(CDI) was filled out by children, Behavior Checklist for Children (CBCL) was filled out by parents and Teacher’s Report Form (TRF) was filled out by teacher.Results: Type I alcoholic group had 25 alcoholic fathers and their children, type II alcoholic group had 10 alcoholics and their children. Accordig to CBCL, agressive behavior was low in type II alcoholics children. Data obtained from TRF, working hard, agressive behavior and total problems were statistically low in type II alcoholics children. Working hard showed strong correlation with learning. Similarly working hard was correlated with academic success, appropiate behavior positively.Conclusion: Children who were in Type I alcoholic group were living problems in agressive behavior and total problem areas. Type II alcoholics children group had more problems in working hard, learning and academic success than type I alcoholics children group according to TRF.
Keywords: Alcoholizm; type; children; academic success